Research Trends on E-Module in Science Learning in SINTA-Indexed Journals within FMIPA UNM: A Literature Review - Usman, Musawwir; Ramlawati; Kisworo, Banu; Annam, Syarful (Pusat Studi Bahasa dan Publikasi Ilmiah, 2025)
E-modules have become an effective technology-based learning medium in 21st century education, offering flexibility, interactivity, and support for independent learning, especially in science education where abstract concepts require visualization. However, research on e-modules in Indonesia remains fragmented across journals, resulting in a lack of clarity regarding research trends and directions. This study aims to map and analyze research trends on e-modules in science education published in SINTA-indexed journals within the Faculty of Mathematics and Natural Sciences (FMIPA) at Universitas Negeri Makassar (UNM). This study employs a literature review method with content analysis of 17 articles published between 2020 and 2024. The findings indicate a growing interest in e-module since 2022, with most studies adopting Research and Development (R&D) approaches using the ADDIE model and quantitative quasi-experimental designs. The main research subjects were expert, teachers, and high school students. The primary instruments used included questionnaires, test, and validation sheets. Data analyses commonly included Gregory’s validity test, practicality tests, N-Gain, and t-tests. Most used or developed e-modules were web-based, particularly in physics and chemistry. Research is still centered in Sulawesi, reflecting the journal’s regional scope. In conclusion, e-module research in science education shows a positive trend, contributing significantly to improving students’ academic performance, motivation, and reading interest, though it remains limited in scope and methodology. Therefore, future studies should broaden coverage across Indonesia, employ more diverse methodologies, and emphasize interactive e-module development to enhance the quality of science learning.